Pengaruh Penyuluhan Terhadap Pengetahuan Tentang Toilet Training Pada Ibu Yang Mempunyai Batita Di Desa Asri Mulya Kecamatan Jorong Kabupaten Tanah Laut Tahun 2017 - Ni Wayan Kurnia Widya Wati; Khalimatus Sa’diyah (HB PRESS, 2018)
Toilet training consists of control of bowel movements, and control urination. A good time to start training a child for toilet training is after the child can start walking (around the age of 1.5 years). The most common impacts of toilet training failures can disrupt the personality of the child in which the child tends to be inferior and unconfident, stubborn, inclined to careless, likes to make fuss, emotional and casual in daily activities. Mothers are very influential on the level of success of children, because the direct mother who helps children learn. In this case, the mother's knowledge of toilet training becomes very important. Of the 5 mothers interviewed there were only 1 mothers who understood toilet training. Given the influence of counseling on the knowledge of toilet training in mothers who have toddlers. Research design is Quasy experiment with one group pretest posttest design. Research subjects are all mothers who have toddlers in the village of Asri Mulya a number of 35 people. Sampling using total sampling.Research time of December-January 2018. Analysis of the data used is Wilcoxon Signed Ranks Test Test. The result of the research shows that there is influence of knowledge about toilet training in mother with toddler in Asri Mulya village (p = 0,000 <0,05). To the mothers is advised to increase the action in teaching toilet training on toddlers who are a fruit in the family